2017
DOI: 10.1039/c7qm00235a
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks meet polymer brushes: enhanced crystalline film growth induced by macromolecular primers

Abstract: We introduce tailor-made polymeric 3D primers, which produce a striking enhancement in MOF film growth compared to traditional primers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…The deposited mass obtained by QCM for a 1x-ZIF-8 film growth cycle is higher than values reported in recent works (see Table S1 for comparison with recently reported methods). 56,66,72,73 This result can be explained by taking into account the high affinity of Zn 2+ ions for the exposed sulfonate moieties present in the PEDOT:PSS layer. It has been demonstrated, the interactions between MOF precursors and surface-exposed moieties are crucial to manipulate the dynamics of film growth.…”
Section: Zif-8 Deposition On the Lbl Assembliesmentioning
confidence: 98%
See 1 more Smart Citation
“…The deposited mass obtained by QCM for a 1x-ZIF-8 film growth cycle is higher than values reported in recent works (see Table S1 for comparison with recently reported methods). 56,66,72,73 This result can be explained by taking into account the high affinity of Zn 2+ ions for the exposed sulfonate moieties present in the PEDOT:PSS layer. It has been demonstrated, the interactions between MOF precursors and surface-exposed moieties are crucial to manipulate the dynamics of film growth.…”
Section: Zif-8 Deposition On the Lbl Assembliesmentioning
confidence: 98%
“…56 Moreover, Bindini et al showed that the use of a sulfonate-bearing polyelectrolyte brush as anchoring platform (a 3d-primer rather than a surface confined 2D-primer) increased the amount of ZIF-8 deposited compared to what could be expected from a sulfonate-terminated SAM. 73 In that work, it was stated that the brushes contain…”
Section: Zif-8 Deposition On the Lbl Assembliesmentioning
confidence: 99%
“…The fact that no additional particles with different size distribution were observed suggest that heterogeneous nucleation within the microgel is greatly enhanced over homogeneous ZIF-8 nucleation. 20 Further evidence of the suggested confined growth can be obtained from DLS autocorrelation curves ( Fig. 1a , inset).…”
Section: Resultsmentioning
confidence: 75%
“…[ 2,9,10 ] Because of the chemical stability, thermal stability and highly adjustable photoelectric properties, as carriers of catalyst, this kind of carbon material have been used for electrochemical applications such as OWS, oxygen evolution reaction (OER), carbon dioxide reduction, and hydrogen evolution reaction (HER). [ 11,12 ] The study also shows that the macrocyclic carbon framework material enhances the crystallization ability of ZIF‐8, [ 13 ] which solves the problem of low crystallinity of metal organic frameworks prepared by traditional benzene derivatives (BZD). As a significant natural and synthetic compound with a macrocyclic skeleton structure, anthraquinone derivatives (AQD) are particularly attractive because they can be extracted from plants, which means economical and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%